Preformulation studies on partially pregelatinized starch prepared from cassava Manihot esculenta Crantz (Family Euphorbiaceae) - Nadales, Gerlie; Pascual, Rhowena; Bautista, Jocelyn (Manila Department of Industrial Pharmacy, College of Pharmacy, University of the Philippines, 1996)
Modified starches are commonly used as binder and disintegrants to tablets prepared by direct compression. The objective of this study is to modify Cassava starch by partial pregelatinization as well as perform preformulation studies to this product.
Starch was partially pregelatinized by dispersing starch in distilled water (42% w/v) and heating it at 62° ? 72°C for 5 minutes, producing a slurry. This slurry is immediately poured on trays, spread thinly and dried at 80° ? 100°C for 1-2 hours. The dried material is the processed to produce the desired particle si
The powder characteristics of the pregelatinized starch were examined and these includes its moisture content, bulk density, flowability and particle size distribution. Tests are then performed to this product to determine if it conforms to the official monograph of Pregelatinized Starch N.F. These tests include organoleptic evaluation, identification test, loss on drying, pH determination, oxidizing substances, sulfur dioxide, moisture content and sieve analysis. The product also undergone preformulation studies to determine its stability and compatibility with other excipien
​Thesis (Bachelor of Science in Industrial Pharmacy)--University of the Philippines, March 1996.
Keywords: Cassa; Star; Kamoteng-kah.